Iceland : Staff Report for the 2012 Article IV Consultation and First Post- Program Monitoring Discussion. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Consultation reports that Iceland's fiscal consolidation is continuing, but at a slower pace. Moderate expenditure overruns materialized in 2011, which will partly spill over to 2012 and the medium term. A key priority is to put the medium-term fiscal path back on track, which can be achieved with additional fiscal measures of 1\2 percent of GDP. Lifting the capital controls remains an overarching policy challenge, given the significant locked-in funds.